Relação com o saber de estudantes do 1º ano do ensino médio integrado : um estudo sobre o sentido atribuído à escola e à aprendizagem de matemática - Pavan, Marília Balbinot (2025)
This dissertation investigated the students’ relationship with knowledge in the integrated technical high school programs at IFRS – Campus Erechim, based on their school experiences, particularly in mathematics classes. The choice of this research topic stems from the researcher’s concerns about the resistance that many students display towards school and, in particular, towards this component of the exact sciences. The research problem is presented by the following question: in what ways do first-year students of the Integrated High School Programs (EMI) at the Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (IFRS) – Campus Erechim expand and enhance their relationship with knowledge based on the experiences they have at school, particularly in mathematics classes? In this regard, our objective is to identify whether the interactions with the campus and with mathematics classes mobilize students to expand their relationship with knowledge and to explore the epistemic, identity-related, and social impact of this relationship on their own constitution. The theoretical framework of this dissertation is primarily based in the studies of Bernard Charlot (2000, 2001, 2005, 2009, 2013, 2022, 2024), more specifically regarding the theory of the relationship with knowledge. Furthermore, to substantiate the role of mathematics in students’ lives, the main theoretical framework is provided by Ubiratan D’Ambrosio (1986, 1998, 2005, 2011, 2012, 2018), who addresses students’ relationship with the process of teaching and learning mathematics. From this theoretical perspective, the relationship with knowledge is understood not to be limited to the comprehension of theories, doctrines, or sciences, as it transcends the mere assimilation of curricular content from school subjects, contributing to the broader cultural formation of the individual and to their social and civic integration. Thus, it is argued that school can (and should) have a profound impact on people’s ways of life. Regarding its nature, this research is characterized as basic, since its focus is on expanding knowledge about the topic rather than on the practical and immediate application of tools for problem-solving. The methodological procedure consisted of applying a questionnaire via Google Forms, which provided quantitative data; thus, the research encompasses both quantitative and qualitative dimensions, since it presents a detailed description of the object of study, conducts data analysis considering relevant theories, and lists results. Initially, the bibliographic research procedure is highlighted, which is conducted based on the texts of Bernard Charlot and Ubiratan D’Ambrosio, followed by data collection through the application of a questionnaire via Google Forms in the institution’s computer lab. The data analysis allowed us to conclude that the majority of the students who participated in the research generate and perceive formative meaning from the relationship they establish with the school environment. Thus, the school proved to be a space capable of promoting students’ epistemic, identity-related, and social constitution. Consequently, through school belonging, there is a productive relationship with others, with oneself, and with one’s own constitution of individuality. There is also the recognition of a relationship with mathematics that strengthens epistemic matters, especially when a positive relationship with the subject teacher is established. In summary, it was concluded that if the school and the relationship with the subjects – in this case, mathematics – are productive, students feel mobilized to expand and engage in their relationships with knowledge.